2000
DOI: 10.4049/jimmunol.164.3.1442
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Lung Surfactant Protein D: Complementary DNA Cloning, Chromosomal Localization, and Tissue Distribution

Abstract: Porcine organs and lung surfactant have medically important applications in both xenotransplantation and therapy. We have started to characterize porcine lung surfactant by cloning the cDNA of porcine surfactant protein D (SP-D). SP-D and SP-A are important mediators in innate immune defense for the lung and possibly other mucosal surfaces. Porcine SP-D will also be an important reagent for use in existing porcine animal models for human lung infections. The complete cDNA sequence of porcine SP-D, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 63 publications
1
33
0
1
Order By: Relevance
“…Characterization of porcine SP-D (pSP-D) by cDNA cloning revealed that pSP-D has structurally unique features that have not been found in SP-D from other species examined to date (26). These include a cysteine within the collagen domain, an insertion of 3 aa in the CRD and the presence of a terminally sialylated N-linked sugar within the CRD (27).…”
Section: Nfluenza a Virus (Iav)mentioning
confidence: 99%
“…Characterization of porcine SP-D (pSP-D) by cDNA cloning revealed that pSP-D has structurally unique features that have not been found in SP-D from other species examined to date (26). These include a cysteine within the collagen domain, an insertion of 3 aa in the CRD and the presence of a terminally sialylated N-linked sugar within the CRD (27).…”
Section: Nfluenza a Virus (Iav)mentioning
confidence: 99%
“…Our investigations into the primary structure and biochemical properties of porcine SP-D (pSP-D) have revealed that pSP-D is unique in that it is the only SP-D species known to be equipped with an N-linked complex sialic acid-rich glycan in its CRD (10,20). These sialic acids are likely to interact with the conserved sialic acid receptor, located on the HA of all IAVs, that mediates binding of the virus to sialoglycans expressed on the respiratory epithelium, initiating IAV infection of the lung.…”
mentioning
confidence: 99%
“…The pSP-D cDNA sequence has been determined, 14 the pSP-D protein has been purified and characterized, 15,16 and the interaction between pSP-D and influenza A virus described. 17,18 Furthermore, pSP-D was found to be immunolocalized in normal tissues (predominantly in Clara cells and in serous cells of the bronchial submucosal glands) and, to a lesser extent, in alveolar type II cells, in epithelial cells of the intestinal glands (crypts of Lieberkühn) in the duodenum, jejunum and ileum, and in serous cells of the dorsolateral lacrimal gland.…”
Section: Introductionmentioning
confidence: 99%